Placental cadmium and its association with maternal diet and offspring growth in Koreans - Kim, Dahyeon; Lee, Cheawon; Kim, Yoon Ha; Choi, Myeong Gyun; Kim, Jong Woon; Park, Clara Yongjoo (Nutrition research and practice, 2025)
Cadmium (Cd) can cross the placental barrier and affect fetal development. Dietary exposure is a primary source of Cd intake. However, studies examining the relationships between food intake, placental Cd concentration, and offspring growth remain limited, especially in Asian populations. This study aimed to identify foods and cooking methods that contribute to placental Cd concentration and assess the association between placental Cd concentration and infant growth. This study analyzed 72 non-smoking pregnant women and their placentas. Food intake during late pregnancy was assessed using a food frequency questionnaire and categorized based on main ingredients and cooking methods. Placental Cd concentration was measured using an inductively coupled plasma mass spectrometer. Neonatal anthropometrics were obtained from medical records, while 1-yr anthropometrics were collected through interviews. Placental Cd concentration was not associated with intakes of foods when categorized according to main ingredients; however, positive associations with the intake of boiled and deep-fried foods were observed (β = 0.350 and 0.739, respectively; both < 0.01). A positive trend was observed between placental Cd concentration and placental efficiency (β: 0.101, = 0.07), while placental Cd concentration was negatively associated with birth weight and length in female infants (β = -19.55 and -1.358, respectively; < 0.05). No significant associations were found between p[Cd] and 1-year growth indicators. Placental Cd concentration may be associated with the consumption of boiled and deep-fried foods during late pregnancy, rather than intake of a certain food group categorized by main ingredient. The observed trend of increased placental efficiency despite lower birth weight and length in female infants suggests that the placenta may function as a barrier to Cd sex-specifically, potentially mitigating its effects on offspring development.